FIGO 2018 stage IB2 (2–4 cm) Cervical cancer treated with Neo-adjuvant chemotherapy followed by fertility Sparing Surgery (CONTESSA); Neo-Adjuvant Chemotherapy and Conservative Surgery in Cervical Cancer to Preserve Fertility (NEOCON-F). A PMHC, DGOG, GCIG/CCRN and multicenter study. Issue 5 (17th May 2019) - Plante, Marie; van Trommel, Nienke; Lheureux, Stephanie; Oza, Amit M; Wang, Lisa; Sikorska, Karolina; Ferguson, Sarah Elizabeth; Han, Kathy; Amant, Frederic
Abstract : Background: There are limited data regarding the optimal management of pre-menopausal women with cervical lesions measuring 2–4 cm who desire to preserve fertility. Primary objectives: To evaluate the feasibility of preserving fertility. Study hypothesis: Neo-adjuvant chemotherapy will be effective in reducing the size of the tumor and will enable fertility-sparing surgery without compromising oncologic outcome. Trial design: Pre-menopausal women diagnosed with stage International Federation of Gynecology and Obstetrics (FIGO) IB2, 2–4 cm cervical cancer who wish to preserve fertility will receive three cycles of platinum/paclitaxel chemotherapy. Patients with complete/partial response will undergo fertility-sparing surgery. Patients will be followed for 3 years to monitor outcome. Patients with suboptimal response (residual lesion ≥2 cm) will receive definitive radical hysterectomy and/or chemoradiation. Major eligibility criteria: Patients must have histologically confirmed invasive cervical cancer, 2–4 cm lesion, by clinical examination and magnetic resonance imaging (MRI), negative node, and pre-menopausal (≤40 years old). Following three cycles of neo-adjuvant chemotherapy, patients must achieve a complete/partial response (residual lesion <2 cm). Exclusion criteria include high-risk histology, tumor extension to uterine corpus/isthmus (as per MRI), and suboptimal response/progression following neo-adjuvant chemotherapy. Primary endpoints: Assess the rate of functional uterus defined as successful fertility-sparing surgery and no adjuvant therapy. Sample size: A total of 90 evaluable patients will be needed to complete the study. Estimated dates for completing accrual and presenting results: Expected complete accrual in 2022 with presentation of results by 2025. Trial registration number: Pending ethics submission.